Perceptions On Halal Labels Impact On Purchase Decisions With Brand Image As Intervening Variables: A Consumer Study Of Solaria Restaurants In Jakarta - Suleman, Dede; Febriyantoro, Mohamad Trio; Fadly, Rachmat; Napitupulu, Rohani Lestari; Safria, Dhuha; Hasibuan, Reza Rahmadi (IJOSMAS, 2022)
This study aims to examine the impact of halal labels on purchasing decisions with brand image as an intervening variable on Solaria restaurant consumers in Jakarta. This quantitative study was conducted using a questionnaire, the questionnaire as a research instrument using a Likert scale. Determination of the research sample using purposive sampling, with the criteria of Solaria restaurant consumers in the last year located in Jakarta and willing to fill out the questionnaire given by the researcher. From the distribution of data, 80 questionnaires were collected which were suitable for further processing. The collected data is processed using SmartPLS software. The results showed that the halal label and brand image had a significant effect on purchasing decisions, brand image brand image was a significant mediating variable between the influence of halal labels on purchasing decisions